[Toyo Ito. 8 obras 6 proyectos] (The Japan Architect. Library, 1993)
El artículo incluye: Shimosuwa Municipal Museum. Shimosuwa-machi. Nagano 1993 / Public Kindergarten at Eckenheim, Frankfurt. Germany / Amusement Complex H. Tokyo, 1993 / Yatsushiro Municipal Museum. Kumamoto, 1991 / Guesthouse for Sapporo Breweries. Eniwa, Hokkaido, 1989 / Gallery U in Yugawara. Ashigarashimo-gun, Kanagawa, 1991.